Prepalensi leptospirosis pada sapi bibit di Pulau Lombok=Prevalence of Leptospirosis in Calves Stock Breeder in Lombok Island - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The objective of the present study was to evaluate the prevalence rate of leptospirosis calves stock breeder in Lombok Island, West Nusa Tenggara considering that Lombok Island is the center for stock breeder and beef cattle to supplys other areas in Indonesia including being exported to Malaysia. An export agreement usually the calves stock breeder must be free from several disease, such as leptospirosis. Approximately one hundred sera samples were collected from four hundred calves stock breeder ranging from 1,5 - 2 years of age that were ready to be sent to other islands. Before sera collected data of ages, breeds, sexes, origins and ear tags were recorded. The calves stock bloods from Lombok Island (West Lombok, Central Lombok and East Lombok), were collected from Jugular vein soon after entering quarantine periode at Balai Karantina Hewan Kelas II Lembar, Mataram. Before examinations performed, the sera were stored at - 20Â° C. The examinations were carried out at the laboratory of Balai Penelitian Veteriner Bogor, by using the so-called serologic microscopic agglutination test. Result showed that the prevalence rate of leptospirosis in calves stock breeder in Lombok Island was moderately high (33 %). Serovar detected on the present study involved L. tarrasovi (22 %), L. hardjo (5 %), L. pomona (1 %) and L.rachmati (2 %). In addition double and triple reactions, i.e one serum (1 %) against L. pomona and L. rachmati, one serum (1 %) against L. tarrasovi, L. rachmati and L. pomona, were respectively found. The prevalence levels of leptospirosis based on the areas were 47,6 %, 28,13 % and 15,38 % in the West, Central and East Lombok, respectively. Key words: Prevalence , leptospirosis, microscopic agglutination test Calves Stock Breeder